Convergent evolution of aposematic coloration in Neotropical poison frogs: a molecular phylogenetic perspective - Vences, M.; Kosuch, J.; Boistel, R.; Haddad, CFB; La Marca, E.; Lotters, S.; Veith, M. (Springer, 2003)
Poison frogs of the family Dendrobatidae contain cryptic as well as brightly colored, presumably aposematic species. The prevailing phylogenetic hypothesis assumes that the aposematic taxa form a monophyletic group while the cryptic species (Colostethus sensu lato) are basal and paraphyletic. Analysis of 86 dendrobatid sequences of a fragment of the 16S rRNA gene resulted in a much more complex scenario, with several clades that contained aposematic as well as cryptic taxa. Monophyly of the aposematic taxa was significantly rejected by SH-tests in an analysis with additional 12S and 16S rDNA fragments and reduced taxon sampling. The brightly colored Allobates femoralis and A. zaparo (Silverstone) comb. nov. (previously Epipedobates) belong in a clade with cryptic species of Colostethus. Additionally, Colostethus pratti was grouped with Epipedobates, and Colostethus bocagei with Cryptophyllobates. In several cases, the aposematic species have general distributions similar to those of their non-aposematic sister groups, indicating multiple instances of regional radiations in which some taxa independently acquired bright color. From a classificatory point of view, it is relevant that the type species of Minyobates, M. steyermarki, resulted as the sister group of the genus Dendrobates, and that species of Mannophryne and Nephelobates formed monophyletic clades, corroborating the validity of these genera. Leptodactylids of the genera Hylodes and Crossodactylus were not unambiguously identified as the sister group of the Dendrobatidae; these were monophyletic in all analyses and probably originated early in the radiation of Neotropical hyloid frogs.
Keywords: Amphibia; Dendrobatidae; Hylodinae; aposematic color; skin toxins; phylogeny